Federacja Rosyjska po wyborach do Dumy Państwowej 2007 r. - Kakareko, Ksenia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The elections to the National Duma (Parliament) in 2007 did not change the system of political forces. The composition of the parliament remained practically the same as before the elections. Yet the results were relatively significant as evidence that the political system is stable: the composition of political forces remained unchanged. The significance of the Duma elected in the course of December 2007 elections is likely to weaken. The Parliament has become even less independent and more subordinate to the executive power. One can venture to say that the Russian Duma is more and more like the USSR Main Board before 1989.